Effects of nano-kaolinite clay on the freeze–thaw resistance of concrete. (September 2015) - Fan, Yingfang; Zhang, Shiyi; Wang, Qi; Shah, Surendra P.
Abstract: This paper investigates the effects of nano-kaolinite clay (NKC) on the freezing and thawing (F–T) behavior of concrete. In our experiments, we substituted NKC for 0%, 1%, 3%, and 5% of mixtures of ordinary Portland, cement, by weight. The blended concrete was prepared using w/c ratio as 0.5. A rapid freeze–thaw Cabinet was then used to measure the resistance of ordinary Portland cement concrete, as opposed to the concrete/NKC mixture, to examine deterioration caused by repeated F–T actions. We regularly measured the properties of the concrete specimens, including the pore structure, mass, electrical resistivity, chloride diffusion coefficient, compressive strength and dynamic modulus of elasticity. A computed tomography scan test evaluated the porosity characteristics of the concrete. This paper also applied scanning electron microscopy and X-ray diffraction tests in order to investigate the micro morphology and chemical element distributions inside of the concrete. The experimental results and visual comparisons revealed that the introduction of NKC improves the F–T resistivity values, as compared to the control concrete. The samples with 5% NKC exhibited the highest compressive strength, chloride diffusion resistivity, relative dynamic modulus of elasticity, and the most electrical resistivity after 125 F–T cycles. We designated the anti-freezing durability coefficient (DF) as the index to assess the F–T resistivity of concrete. The following research discusses the relationship between the concrete's DF and the number of F–T cycles, compressive strength, chloride diffusion coefficient, and the electrical resistivity of the concrete samples.